Secondary battery, preparation method thereof and electric device
By introducing an inorganic material layer into the separator to absorb lithium dendrites, the problem of lithium dendrites piercing the separator is solved, thereby improving the high-rate cycle performance and safety of the secondary battery.
Patent Information
- Application Number
- CN202410458125.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-16
- Publication Date
- 2025-10-24
AI Technical Summary
In existing secondary batteries, lithium dendrites puncture the separator during cycling, causing short circuits and affecting the cycle performance and safety performance of high-rate batteries.
Inorganic material layers, including lithium aluminum titanium phosphate, are introduced into the membrane to absorb lithium dendrites, reducing the risk of lithium dendrites piercing the membrane. The ion transport performance and mechanical strength of the membrane are also improved by controlling the porosity and material distribution.
It improves the battery's cycle performance and safety at high rates, reduces the risk of lithium dendrites piercing the separator, and enhances the overall ion transport uniformity and compatibility of the separator.
Smart Images

Figure CN120834381A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery, a preparation method thereof, and an electric device. BACKGROUND
[0002] In recent years, with the application range of secondary batteries becoming more and more extensive, secondary batteries are widely used in energy storage power supply systems such as hydroelectric, thermal, wind and solar power stations, and in many fields such as electric tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, etc. Due to the great development of secondary batteries, higher requirements are put forward for the cycle performance. However, the cycle performance of the existing secondary batteries needs to be further improved. SUMMARY
[0003] The present application is made in view of the above problems, and aims to provide a secondary battery with good cycle performance.
[0004] The first aspect of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, the separator being located between the positive electrode sheet and the negative electrode sheet, the separator comprising a first polymer layer and a material layer arranged on the first polymer layer, the material layer comprising an inorganic material,
[0005] The inorganic material comprises one or more of lithium titanium aluminum phosphate, lithium germanium aluminum phosphate, lithium titanium germanium aluminum phosphate, lithium titanium tantalum aluminum phosphate, lithium tetra-thiophosphate, lithium germanium phosphorus sulfide, lithium phosphorus sulfide chloride, iron oxide, copper oxide, titanium dioxide, tin dioxide, manganese dioxide, zinc oxide, zirconium dioxide, chromium nitride, vanadium nitride, nickel nitride, iron nitride, graphene oxide, graphite oxide, fluorinated graphite, fluorinated graphene, fluorinated carbon nanotubes, and fluorinated carbon fibers.
[0006] By arranging the inorganic material of lithium titanium aluminum phosphate, lithium germanium aluminum phosphate, lithium titanium germanium aluminum phosphate, lithium titanium tantalum aluminum phosphate, lithium tetra-thiophosphate, lithium germanium phosphorus sulfide, lithium phosphorus sulfide chloride, iron oxide, copper oxide, titanium dioxide, tin dioxide, manganese dioxide, zinc oxide, zirconium dioxide, chromium nitride, vanadium nitride, nickel nitride, iron nitride, graphene oxide, graphite oxide, fluorinated graphite, fluorinated graphene, fluorinated carbon nanotubes or fluorinated carbon fibers in the material layer of the separator, the above inorganic material can react with lithium metal, absorb the lithium dendrites in contact with the material layer, change the sharp lithium dendrites into other lithium compounds, reduce the risk of lithium dendrites continuing to pierce the separator, and improve the cycle performance of the battery at high rate.
[0007] In any embodiment, the material layer is arranged on the side surface of the first polymer layer close to the negative electrode sheet.
[0008] The material layer in the diaphragm is arranged on one side surface of the first polymer layer close to the negative electrode tab, the inorganic material can quickly react with lithium dendrites growing on the negative electrode tab to achieve the purpose of absorbing lithium dendrites, and the cycle performance of the battery under high rate is improved.
[0009] In any embodiment, in a longitudinal section view of the diaphragm, the difference between the porosity of the material layer and the porosity of the first polymer layer is less than or equal to 10%.
[0010] The difference between the porosities of the material layer and the first polymer layer is small, the difference in the transmission capacity of lithium ions in different layers is small, the difference in the lithium ion concentration between the layers is small, which is beneficial to the uniformity of ion transmission of the diaphragm as a whole, and the difference in the porosities between the layers is small, which can also reduce the interface effect between the layers of the diaphragm, improve the compatibility between the layers of the diaphragm, reduce the impedance of the diaphragm, and improve the cycle performance and rate performance of the battery.
[0011] In any embodiment, in a longitudinal section view of the diaphragm, the porosity of the material layer is 10%-30%.
[0012] The porosity of the material layer is within a suitable range, which ensures that the material layer has excellent ion transmission performance, the diaphragm has low impedance, and at the same time, the material layer and the diaphragm have certain mechanical strength, thereby comprehensively improving the use performance of the diaphragm.
[0013] In any embodiment, in a longitudinal section view of the diaphragm, the porosity of the first polymer layer is 10%-30%.
[0014] The porosity of the first polymer layer is within a suitable range, which ensures that the first polymer layer has excellent ion transmission performance, the diaphragm has low impedance, and at the same time, the first polymer layer and the diaphragm have certain mechanical strength, thereby comprehensively improving the use performance of the diaphragm.
[0015] In any embodiment, the diaphragm further comprises a second polymer layer, and the material layer is located between the first polymer layer and the second polymer layer.
[0016] The first polymer layer and the second polymer layer are arranged on the two sides of the material layer, respectively, which can protect the material layer, reduce the risk of early reduction and early failure of the inorganic material caused by direct contact between the inorganic material and the negative electrode tab, and at the same time, improve the safety factor of the material layer and the diaphragm, thereby further improving the cycle performance of the battery under high rate.
[0017] In any embodiment, the difference between the porosity of the material layer and the porosity of the first polymer layer is less than or equal to 10% and / or the difference between the porosity of the material layer and the porosity of the second polymer layer is less than or equal to 10%.
[0018] The difference in the amount of pores between the layers is small, the difference in the transport capacity of lithium ions in different layers is small, and the difference in the lithium ion concentration between the layers is small, which is beneficial to the uniformity of ion transport of the entire separator. In addition, the small difference in the amount of pores between the layers can also reduce the interface effect between the layers of the separator, improve the compatibility between the layers of the separator, reduce the impedance of the separator, and be beneficial to improving the cycle performance and rate performance of the battery.
[0019] In any embodiment, in a longitudinal section view of the separator, the amount of pores of the material layer is 10%-30%.
[0020] The amount of pores of the material layer is within a suitable range, which not only ensures that the material layer has excellent ion transport performance and the separator has low impedance, but also enables the material layer and the separator to have certain mechanical strength, thereby comprehensively improving the use performance of the separator.
[0021] In any embodiment, in a longitudinal section view of the separator, the amount of pores of the first polymer layer and / or the amount of pores of the second polymer layer is 10%-30%.
[0022] The amount of pores of the first polymer layer and / or the amount of pores of the second polymer layer is within a suitable range, which not only ensures that the first polymer layer and the second polymer layer have excellent ion transport performance and the separator has low impedance, but also enables the first polymer layer, the second polymer layer and the separator to have certain mechanical strength, thereby comprehensively improving the use performance of the separator.
[0023] In any embodiment, the volume distribution particle size Dv50 of the inorganic material is 50 nm-5000 nm.
[0024] In any embodiment, the volume distribution particle size Dv50 of the inorganic material is 50 nm-1000 nm.
[0025] The volume distribution particle size Dv50 of the inorganic material is within a suitable range, which on the one hand reduces the risk of particles with too small particle size blocking the pores on the surface of the material layer, enables the separator to have excellent air permeability, and enables the separator to have excellent ion transport channels. On the other hand, it also does not bring about adverse effects on the processability due to the particle size of the inorganic material being too large, improves the uniformity of the distribution of the inorganic material in the material layer, and at the same time, reduces the phenomenon of "powder falling" of the inorganic material with too large particle size during the process, thereby affecting the effect of the inorganic material absorbing lithium dendrites.
[0026] In any embodiment, the material layer further comprises a third polymer, the mass content of the inorganic material is 5%-50% based on the mass of the material layer; and / or, the mass content of the third polymer is 50%-95%.
[0027] In any embodiment, the mass content of the inorganic material is 10%-50% based on the mass of the material layer; and / or, the mass content of the third polymer is 50%-90%.
[0028] Controlling the mass content of the third polymer or the inorganic material in the material layer within a suitable range, the separator has low ion impedance, and the battery has good cycle performance at high rate.
[0029] In any embodiment, the first polymer layer further comprises a first polymer, and the second polymer layer further comprises a second polymer,
[0030] The first polymer, the second polymer, and the third polymer each independently comprise one or more of polyethylene, polypropylene, polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl chloride.
[0031] In any embodiment, the first polymer, the second polymer, and the third polymer comprise polymers of the same material.
[0032] The first polymer, the second polymer, and the third polymer are polymers of the same material, the separator has good compatibility, improves the transmission speed of lithium ions in the separator, reduces the ion impedance of the separator, and improves the cycle performance and rate performance of the battery.
[0033] In any embodiment, the thickness ratio of the first polymer layer, the material layer, and the second polymer layer is 1:(1-3):(0.8-1.2).
[0034] In any embodiment, the thickness ratio of the first polymer layer, the material layer, and the second polymer layer is 1:(1.5-2.5):(0.8-1.2).
[0035] The thickness ratio of the first polymer layer, the material layer, and the second polymer layer is within a suitable range, the separator has low ion impedance, and the battery has good cycle performance at high rate.
[0036] In any embodiment, the thickness of the first polymer layer is 2.5-4.5 μm; and / or, the thickness of the material layer is 3.5-7.5 μm; and / or, the thickness of the second polymer layer is 2.5-4.5 μm.
[0037] The first polymer layer, the material layer, or the second polymer layer is within a suitable range, the separator has low ion impedance, the separator has a certain puncture strength, and the battery has good cycle performance and safety performance at high rate.
[0038] In any embodiment, the thickness of the separator is 5-25 pm.
[0039] In any embodiment, the thickness of the separator is 10-15 pm.
[0040] The second aspect of the present application provides a preparation method of a secondary battery, comprising:
[0041] Assembling an electrode assembly comprising a positive electrode sheet, a negative electrode sheet and a separator to obtain a secondary battery, the separator comprising a first polymer layer and a material layer arranged on the first polymer layer, the material layer comprising an inorganic material,
[0042] The inorganic material comprises one or more of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium aluminum titanium germanium phosphate, lithium aluminum titanium tantalum phosphate, lithium tetrathiophosphate, lithium germanium phosphorus sulfide sulfide, lithium phosphorus sulfur chloride sulfide, iron oxide, copper oxide, titanium dioxide, tin dioxide, manganese dioxide, zinc oxide, zirconium dioxide, chromium nitride, vanadium nitride, nickel nitride, iron nitride, graphene oxide, graphite oxide, fluorinated graphite, fluorinated graphene, fluorinated carbon nanotubes, fluorinated carbon fibers.
[0043] The material layer in the separator of the secondary battery absorbs lithium dendrites in contact with the material layer, changes sharp lithium dendrites into other lithium compounds, reduces the risk of lithium dendrites continuing to pierce the separator, and improves the cycle performance of the battery at high rate.
[0044] In any embodiment, the preparation method of the separator is as follows:
[0045] Step a: using a co-extrusion process to obtain a composite sheet layer from a first polymer layer raw material, a material layer raw material and a second polymer layer raw material;
[0046] Step b: stretching the composite sheet layer to form a film;
[0047] Step c: extracting and heat setting the film to obtain a separator.
[0048] The material layer raw material comprises the inorganic material,
[0049] The separator comprises a first polymer layer, a material layer and a second polymer layer, and the material layer is located between the first polymer layer and the second polymer layer.
[0050] The separator obtained by the preparation method can include a first polymer layer, a material layer and a second polymer layer, the material layer includes an inorganic material capable of reacting with lithium metal, so that the sharp lithium dendrites are converted into other lithium compounds, reducing the risk of lithium dendrites continuing to pierce the separator, improving the cycle performance of the battery at high rate, and the material layer is located between the first polymer layer and the second polymer layer, which can improve the safety performance of the material layer and further improve the cycle performance of the battery.
[0051] The third aspect of the present application is a power consumption device, characterized in that it includes the secondary battery of the first aspect or the secondary battery obtained by the preparation method of the second aspect. BRIEF DESCRIPTION OF DRAWINGS
[0052] Figure 1 is a schematic diagram of a separator according to an embodiment of the present application;
[0053] Figure 2 is a schematic diagram of a separator according to an embodiment of the present application
[0054] Figure 3 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0055] Figure 4 is Figure 3 is an exploded view of the secondary battery according to an embodiment of the present application shown in FIG. 3;
[0056] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application;
[0057] Figure 6 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0058] Figure 7 is Figure 6 is an exploded view of the battery pack according to an embodiment of the present application shown in FIG. 7;
[0059] Figure 8 is a schematic diagram of a power consumption device using the secondary battery according to an embodiment of the present application as a power source;
[0060] Figure 9 is a scanning electron microscope image of the cross section of the separator prepared in Example 18;
[0061] Figure 10 is a scanning electron microscope image of the cross section of the separator prepared in Example 18;
[0062] Figure 11 is a scanning electron microscope image of the cross section of the separator prepared in Example 1;
[0063] Figure 12 is a scanning electron microscope image of the cross section of the separator prepared in Example 1.
[0064] Reference Signs:
[0065] 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 case; 52 electrode assembly; 53 cover plate; 10 separator; 101 first polymer layer; 102 material layer; 103 second polymer layer. DETAILED DESCRIPTION
[0066] Hereinafter, specific embodiments of the secondary battery and the method of manufacturing the same, and the electric device according to the present application are described in detail with appropriate reference to the accompanying drawings. However, there can be cases where unnecessary detailed description is omitted. For example, there can be cases where detailed description of matters well known in the art, repeated description of substantially identical structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand the present application, and are not intended to limit the subject matter recited in the claims.
[0067] The "range" disclosed in the present application is defined in the form of lower and upper limits, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, i.e., any lower limit can be combined with any upper limit to form a range. For example, if the ranges 60-120 and 80-110 are listed for a particular parameter, it is understood that the ranges 60-110 and 80-120 are also contemplated. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4, and 5 are listed, the following ranges are all contemplated: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In the present application, unless otherwise stated, a numerical range "a-b" represents a shorthand manner of describing each and every numerical value that is within the range, wherein a and b are both real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed herein, and "0-5" is merely a shorthand manner of describing these numerical combinations. In addition, when it is stated that a parameter is an integer ≥ 2, it is equivalent to disclose that the parameter is, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0068] If not specifically stated, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions.
[0069] If not specifically stated, all technical features and optional technical features of the present application can be combined with each other to form new technical solutions.
[0070] If not specified otherwise, all steps of the present application can be performed in sequence or randomly, preferably in sequence. For example, the method comprising steps (a) and (b) means that the method can comprise steps (a) and (b) in sequence, or steps (b) and (a) in sequence. For example, the method comprising step (c) means that step (c) can be added to the method in any sequence, for example, the method can comprise steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.
[0071] If not specified otherwise, the terms "comprising" and "including" as used in the present application are open terms. For example, the terms "comprising" and "including" can mean that other components can also be included or comprised.
[0072] If not specified otherwise, the term "or" in the present application is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following satisfy the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0073] With the development of the current society, people's requirements for the safety of secondary batteries are also getting higher and higher. However, after multiple cycles, metal lithium will be deposited on the surface of the negative electrode, and the metal lithium dendrites will pierce the separator, causing the positive and negative electrodes to contact each other, resulting in a short circuit of the battery, especially during fast charging, dendrites are particularly prone to occur, affecting the cycle performance and safety performance of high-rate batteries.
[0074] [Secondary battery]
[0075] The present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, the separator is located between the positive electrode sheet and the negative electrode sheet, the separator comprises a first polymer layer and a material layer arranged on the first polymer layer, the material layer comprises an inorganic material,
[0076] The inorganic material comprises one or more of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium titanium germanium aluminum phosphate, lithium titanium tantalum aluminum phosphate, lithium tetrathiophosphate, lithium germanium phosphorus sulfide, lithium phosphorus sulfide chloride, iron oxide, copper oxide, titanium dioxide, tin dioxide, manganese dioxide, zinc oxide, zirconium dioxide, chromium nitride, vanadium nitride, nickel nitride, iron nitride, graphene oxide, graphite oxide, fluorinated graphite, fluorinated graphene, fluorinated carbon nanotubes, and fluorinated carbon fibers.
[0077] Figure 1is a schematic diagram of an embodiment of the separator of the present application, the separator 10 comprises a first polymer layer 101 and a material layer 102 disposed on the first polymer layer 101.
[0078] In the present context, the term "graphene oxide" refers to graphene with oxygen-containing functional groups, including but not limited to hydroxyl, carboxyl groups, which can be obtained by oxidizing graphene.
[0079] In the present context, the term "graphite oxide" refers to graphite with oxygen-containing functional groups, including but not limited to hydroxyl, carboxyl groups, which can be obtained by oxidizing graphene.
[0080] In the present context, the term "fluorinated graphite" refers to graphite with fluorine atoms, which can be obtained by reacting graphite with F2.
[0081] In the present context, the term "fluorinated graphene" refers to graphene with fluorine atoms, which can be obtained by reacting graphene with F2.
[0082] In the present context, the term "fluorinated carbon nanotube" refers to carbon nanotube with fluorine atoms, which can be obtained by reacting carbon nanotube with F2.
[0083] In the present context, the term "fluorinated carbon fiber" refers to carbon fiber with fluorine atoms, which can be obtained by reacting carbon fiber with F2.
[0084] In some embodiments, the number ratio of carbon atoms to oxygen atoms in the graphene oxide or graphite oxide is 1:2-2:1.
[0085] In some embodiments, the number ratio of carbon atoms to fluorine atoms in the fluorinated graphite, fluorinated graphene, fluorinated carbon nanotube or fluorinated carbon fiber is 1:2-2:1.
[0086] By disposing inorganic materials of titanium aluminum lithium phosphate, germanium aluminum lithium phosphate, titanium germanium aluminum lithium phosphate, titanium tantalum aluminum lithium phosphate, lithium tetra thiophosphate, lithium germanium phosphorus sulfide sulfide, lithium phosphorus sulfur chloride sulfide, iron oxide, copper oxide, titanium dioxide, tin dioxide, manganese dioxide, zinc oxide, zirconium dioxide, chromium nitride, vanadium nitride, nickel nitride, iron nitride, graphene oxide, graphite oxide, fluorinated graphite, fluorinated graphene, fluorinated carbon nanotube or fluorinated carbon fiber in the material layer of the separator, the above inorganic materials can react with lithium metal, absorb the lithium dendrites in contact with the material layer, change the sharp lithium dendrites into other lithium compounds, reduce the risk of lithium dendrites continuing to pierce the separator, and improve the cycle performance of the battery at high rate.
[0087] In some embodiments, the material layer is disposed on the side surface of the first polymer layer close to the negative electrode tab.
[0088] The material layer in the separator is arranged on a side surface of the first polymer layer close to the negative electrode tab. The inorganic material can quickly react with lithium dendrites growing on the negative electrode tab to achieve the purpose of absorbing lithium dendrites and improve the cycle performance of the battery at high rate.
[0089] In some embodiments, in a longitudinal section view of the separator, the difference between the porosity of the material layer and the porosity of the first polymer layer is less than or equal to 10%.
[0090] In some embodiments, in a longitudinal section view of the separator, the difference between the porosity of the material layer and the porosity of the first polymer layer is less than or equal to 10%, optionally less than or equal to any one of 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, and 10%.
[0091] The porosity can be tested using any known method in the art. For example, the battery is disassembled to obtain the separator, the separator is cut into a sample of a certain size (e.g., 6 mm x 6 mm), the sample is clamped between two conductive and heat-conductive sheets (e.g., copper foil), the sample and the sheets are fixed by adhesive (e.g., double-sided tape), a flat iron block of a certain mass (e.g., 400 g) is pressed for a certain time (e.g., 1 hour) to make the gap between the sample and the copper foil as small as possible, then the edges are trimmed with scissors and fixed on a sample stage with conductive adhesive, and the sample slightly protrudes from the edge of the sample stage. Then the sample stage is locked into the sample holder, the argon ion cross-section polisher (e.g., IB-19500CP) is turned on and vacuumed (e.g., 10 Pa-4 Pa), the argon flow (e.g., 0.15 MPa) and voltage (e.g., 8 KV) are set, and the polishing time (e.g., 2 hours) is set, the sample stage is adjusted to the swing mode and the polishing is started. After polishing, the scanning electron microscope (e.g., ZEISS Sigma300) is used to obtain the scanning electron microscope image of the ion polished cross-section morphology (CP) of the sample, the ImageJ software is used to perform gray value segmentation on the obtained scanning electron microscope image, the area with a gray value of 0-115 is defined as the pore area, and the area with a gray value greater than 115 is defined as the particle area. The area ratio of the pore area to the entire image is calculated to obtain the porosity. During testing, 10 representative scanning images can be randomly selected for porosity testing, and then the average value is taken to obtain the porosity of the sample.
[0092] The difference in the amount of pores between the material layer and the first polymer layer is small, the difference in the transport capacity of lithium ions in different film layers is small, the difference in the lithium ion concentration between the layers is small, which is conducive to the uniformity of ion transport of the whole separator film. At the same time, the difference in the amount of pores between the layers is small, which can also reduce the interface effect between the layers of the separator, improve the compatibility between the layers of the separator, reduce the impedance of the separator, and improve the cycle performance and rate performance of the battery.
[0093] In some embodiments, in the longitudinal section view of the separator, the amount of pores of the material layer is 10%-30%. In some embodiments, in the longitudinal section view of the separator, the amount of pores of the material layer can be selected as 10%, 15%, 20%, 25%, 30% or a numerical range between any two of them.
[0094] The amount of pores of the material layer is within a suitable range, which ensures that the material layer has excellent ion transport performance, the separator has low impedance, and at the same time, the material layer and the separator have certain mechanical strength, which comprehensively improves the use performance of the separator.
[0095] In some embodiments, in the longitudinal section view of the separator, the amount of pores of the first polymer layer is 10%-30%. In some embodiments, in the longitudinal section view of the separator, the amount of pores of the first polymer layer can be selected as 10%, 15%, 20%, 25%, 30% or a numerical range between any two of them.
[0096] The amount of pores of the first polymer layer is within a suitable range, which ensures that the first polymer layer has excellent ion transport performance, the separator has low impedance, and at the same time, the first polymer layer and the separator have certain mechanical strength, which comprehensively improves the use performance of the separator.
[0097] In some embodiments, the separator further comprises a second polymer layer, and the material layer is located between the first polymer layer and the second polymer layer.
[0098] Figure 2 is a schematic diagram of an embodiment of the separator of the present application, the separator 10 comprises a first polymer layer 101, a material layer 102 and a second polymer layer 103, and the material layer 102 is located between the first polymer layer 101 and the second polymer layer 103.
[0099] The first polymer layer and the second polymer layer are respectively arranged on both sides of the material layer, which can protect the material layer, reduce the risk of early reduction and early failure of the inorganic material caused by direct contact between the inorganic material and the negative electrode sheet, and at the same time, can improve the safety factor of the material layer and the separator, and further improve the cycle performance of the battery at high rate.
[0100] In some embodiments, in the longitudinal section view of the separator, the difference between the porosity of the material layer and the porosity of the first polymer layer is less than or equal to 10%, and / or the difference between the porosity of the material layer and the porosity of the second polymer layer is less than or equal to 10%.
[0101] In some embodiments, in the longitudinal section view of the separator, the difference between the porosity of the material layer and the porosity of the first polymer layer is less than or equal to 10%, optionally less than or equal to any one of 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0102] In some embodiments, in the longitudinal section view of the separator, the difference between the porosity of the material layer and the porosity of the second polymer layer is less than or equal to 10%, optionally less than or equal to any one of 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0103] In some embodiments, in the longitudinal section view of the separator, the porosity of the material layer is 10%-30%. In some embodiments, in the longitudinal section view of the separator, the porosity of the material layer is optionally 10%, 15%, 20%, 25%, 30%, or a numerical range between any two of them.
[0104] The porosity of the material layer is within a suitable range, which ensures that the material layer has excellent ion transmission performance, the separator has low impedance, and at the same time, the material layer and the separator have certain mechanical strength, thereby comprehensively improving the use performance of the separator.
[0105] In some embodiments, in the longitudinal section view of the separator, the porosity of the first polymer layer is 10%-30%.
[0106] In some embodiments, in the longitudinal section view of the separator, the porosity of the first polymer layer is optionally 10%, 15%, 20%, 25%, 30%, or a numerical range between any two of them.
[0107] The porosity of the first polymer layer is within a suitable range, which ensures that the first polymer layer has excellent ion transmission performance, the separator has low impedance, and at the same time, the first polymer layer and the separator have certain mechanical strength, thereby comprehensively improving the use performance of the separator.
[0108] In some embodiments, in the longitudinal section view of the separator, the porosity of the second polymer layer is 10%-30%.
[0109] In some embodiments, the second polymer layer has a porosity of 10%, 15%, 20%, 25%, 30%, or any range between any two of the aforementioned values.
[0110] The porosity of the second polymer layer is within a suitable range, which ensures that the second polymer layer has excellent ion transmission performance, the separator has low impedance, and at the same time, the second polymer layer and the separator have certain mechanical strength, thereby comprehensively improving the use performance of the separator.
[0111] In some embodiments, the inorganic material comprises one or more of lithium titanium aluminum phosphate, lithium germanium aluminum phosphate, lithium titanium germanium aluminum phosphate, lithium titanium tantalum aluminum phosphate, lithium tetra-thiophosphate, lithium germanium phosphorus sulfide sulfide, lithium phosphorus sulfide chloride sulfide, graphene oxide, graphite oxide, fluorinated graphite, fluorinated graphene, fluorinated carbon nanotube, and fluorinated carbon fiber.
[0112] The inorganic material of lithium titanium aluminum phosphate, lithium germanium aluminum phosphate, lithium titanium germanium aluminum phosphate, lithium titanium tantalum aluminum phosphate, lithium tetra-thiophosphate, lithium germanium phosphorus sulfide sulfide, and lithium phosphorus sulfide chloride sulfide has good ion conductivity and low electronic conductivity, good ion conduction capacity and electronic insulation, in addition, the inorganic material of graphene oxide, graphite oxide, fluorinated graphite, fluorinated graphene, fluorinated carbon nanotube, and fluorinated carbon fiber has high lithium intercalation capacity, can absorb a large amount of lithium dendrites, and the reaction product with lithium dendrites includes lithium fluoride or lithium oxide, which has good ion conductivity. When the above-mentioned materials are used as lithium dendrite absorbing materials, the impedance of the separator is not greatly increased, and the transfer of electrons through the separator is inhibited, which is beneficial to improve the cycle performance of the battery.
[0113] In some embodiments, the inorganic material has a volume distribution particle size Dv50 of 50 nm to 5000 nm, which can be 50 nm to 1000 nm.
[0114] In some embodiments, the inorganic material has a volume distribution particle size Dv50 of 50 nm, 100 nm, 500 nm, 1000 nm, 1500 nm, 2000 nm, 2500 nm, 3000 nm, 3500 nm, 4000 nm, 4500 nm, 5000 nm, or any range between any two of the aforementioned values.
[0115] In this context, the term "Dv50" refers to the particle size corresponding to the cumulative volume distribution of particles reaching 50% in the particle size distribution curve.
[0116] In the present application, the volume distribution particle size Dv50 of the inorganic material can be tested by a method known in the art, for example, referring to GB / T 19077-2016, and determined by a laser particle size analyzer. The testing instrument can be a Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK.
[0117] The volume distribution particle size Dv50 of the inorganic material within a suitable range, on the one hand, reduces the risk of too small particle size of the inorganic material to block the pores on the surface of the material layer, so that the separator has excellent air permeability and excellent ion transmission channel, and on the other hand, does not bring adverse effects on the processability due to too large particle size of the inorganic material, improves the uniformity of the distribution of the inorganic material in the material layer, and also reduces the phenomenon of "powder falling" of the inorganic material with too large particle size during the process, which affects the effect of absorbing lithium dendrites by the inorganic material.
[0118] In some embodiments, the material layer further comprises a third polymer, and the mass content of the inorganic material is 5%-50%, or optionally 10%-50%, based on the mass of the material layer.
[0119] In some embodiments, the mass content of the inorganic material is optionally 5%, 10%, 20%, 30%, 40%, 50%, or any numerical range between any two of them, based on the mass of the material layer.
[0120] The mass content of the inorganic material within a suitable range ensures that there is enough inorganic material in the material layer for absorbing lithium dendrites, so as to improve the cycle performance of the battery at high rate, and at the same time, reduces the influence of too much inorganic material content on the compatibility between the first polymer layer or the second polymer layer and the material layer, reduces the interface effect, reduces the ion impedance of the separator, and improves the cycle performance and rate performance of the battery.
[0121] In some embodiments, the mass content of the third polymer is 50%-95%, or optionally 50%-90%, based on the mass of the material layer.
[0122] In some embodiments, the mass content of the third polymer is optionally 50%, 60%, 70%, 80%, 90%, 95%, or any numerical range between any two of them, based on the mass of the material layer.
[0123] The mass content of the third polymer within a suitable range ensures that the material layer has good compatibility with the first polymer layer or the second polymer layer, reduces the interface effect, reduces the ion impedance of the separator, improves the cycle performance and rate performance of the battery, and at the same time, makes the material layer have a certain content of inorganic material for absorbing lithium dendrites.
[0124] In some embodiments, the first polymer layer further comprises a first polymer, and the second polymer layer further comprises a second polymer,
[0125] wherein the first polymer, the second polymer, and the third polymer each independently comprises one or more of polyethylene, polypropylene, polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl chloride.
[0126] In some embodiments, the first polymer, the second polymer, and the third polymer each independently comprises any one or more of medium density polyethylene, high density polyethylene, and ultra-high density polyethylene.
[0127] In some embodiments, the medium density polyethylene has a weight average molecular weight of 1.5-2 million.
[0128] In some embodiments, the high density polyethylene has a weight average molecular weight of 2-4 million.
[0129] In some embodiments, the ultra-high density polyethylene has a weight average molecular weight of greater than 10 million.
[0130] In some embodiments, the first polymer, the second polymer, and the third polymer comprise polymers of the same material.
[0131] The first polymer, the second polymer, and the third polymer are polymers of the same material, and the separator has good compatibility, which improves the transmission speed of lithium ions in the separator, reduces the ion impedance of the separator, and improves the cycle performance and rate performance of the battery.
[0132] In some embodiments, the thickness ratio of the first polymer layer, the material layer, and the second polymer layer is 1:(1-3):(0.8-1.2), which can be optionally 1:(1.5-2.5):(0.8-1.2).
[0133] In some embodiments, the thickness ratio of the first polymer layer, the material layer, and the second polymer layer can be 1:1:1, 1:1.5:1, 1:2:1, 1:2.5:1, 1:3:1, 1:1:0.8, 1:1.5:1.2, 1:2:0.9, 1:2.5:0.8, 1:3:1.2, or any numerical range between any two of them.
[0134] The thickness ratio of the first polymer layer, the material layer, and the second polymer layer in the separator can be tested using any method known in the art. For example, a scanning electron microscope (SEM) image of the separator is obtained by referring to the test method for testing the pore volume of the film layer described above, and the thickness of each layer is tested from the SEM image, and thus the thickness ratio of the first polymer layer, the material layer, and the second polymer layer is obtained.
[0135] The thickness of the intermediate layer material layer with the function of absorbing lithium dendrites is within a suitable range, on the one hand, the absorption degree of the material layer to lithium dendrites is as high as possible, and the lithium dendrites are prevented from continuing to grow and piercing the separator, on the other hand, the polymer on both sides provides a certain protection function, and meanwhile, the difference in the thickness of the polymer layers on both sides is small, the ion transmission uniformity of lithium ions in the separator is improved, the phenomenon of local ion concentration difference between layers of the separator is reduced, and the cycle performance and rate performance of the battery are comprehensively improved.
[0136] In some embodiments, the thickness of the first polymer layer is 2.5 μm-4.5 μm. In some embodiments, the thickness of the first polymer layer can be selected as 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, or a numerical range between any two of them.
[0137] In some embodiments, the thickness of the material layer is 3.5 μm-7.5 μm. In some embodiments, the thickness of the material layer can be selected as 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, 7.5 μm, or a numerical range between any two of them.
[0138] In some embodiments, the thickness of the second polymer layer is 2.5 μm-4.5 μm. In some embodiments, the thickness of the second polymer layer can be selected as 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, or a numerical range between any two of them.
[0139] The thicknesses of the first polymer layer, the material layer, and the second polymer layer are controlled within a suitable range, so that the material layer can play the purpose of absorbing the lithium-absorbing material, and the first polymer layer and the second polymer layer on both sides can play the respective protection functions, and the electrochemical performance and safety performance of the battery are comprehensively improved.
[0140] In some embodiments, the thickness of the separator is 5 μm-25 μm, and can be selected as 10 μm-15 μm.
[0141] In some embodiments, the thickness of the separator can be selected as 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, 16 μm, 18 μm, 20 μm, 22 μm, 25 μm, or a numerical range between any two of them.
[0142] The thickness of the separator is within a suitable range, the separator has low ion impedance, and meanwhile, the separator has a certain mechanical strength, and the battery has good cycle performance and safety performance under high rate.
[0143] In some embodiments, the first polymer layer and / or the second polymer layer further comprises an antioxidant.
[0144] In some embodiments, the antioxidant comprises one or more of tris(2,4-di-tert-butylphenyl) phosphite, triphenyl phosphite, n-octadecyl beta-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, [tetra-beta-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester.
[0145] The polymer layers on both sides containing the antioxidant can effectively reduce the thermal oxidation and photo-oxidation reaction rate of the polymer layer, significantly improve the heat resistance and light resistance of the polymer layer, delay the degradation and aging process of the polymer layer, and prolong the service life of the separator.
[0146] In some embodiments, the ion resistance of the separator is less than or equal to 0.40 Ω·cm. In some embodiments, the ion resistance of the separator is any one of less than or equal to 0.40 Ω·cm, less than or equal to 0.35 Ω·cm, less than or equal to 0.30 Ω·cm, less than or equal to 0.25 Ω·cm, less than or equal to 0.20 Ω·cm, less than or equal to 0.15 Ω·cm.
[0147] The ion resistance of the separator can be tested using any method known in the art. For example, the separator to be tested is cut to the same size (45.3 x 33.7 mm), and the separator is placed in an environment of 60°C for baking for more than 4 hours, and then quickly transferred to a glove box; a blank symmetrical battery is assembled using Cu foils as current collectors, with green adhesive having a hole diameter of 14 mm interposed between the Cu foils, and an aluminum plastic film packaging bag is baked at 60°C for more than 4 hours before use, and then quickly transferred to a glove box; a symmetrical battery having different numbers of layers (1, 2, 3, 4, 5 layers) of the separator is assembled in situ in the glove box using a negative electrode as an electrode (5 parallel samples are assembled for each number of layers); the aluminum plastic film packaging bag is side-sealed using a simple packaging machine, 300 μL of electrolyte is injected, and then bottom-sealed; the assembled symmetrical battery is placed in a glove box overnight to allow the electrolyte to fully soak the separator; before measuring EIS, the symmetrical battery with different numbers of layers of the separator is placed in a high-low temperature box for constant temperature for half an hour, and EIS is measured at the set temperature (if it is low temperature, the constant temperature time can be correspondingly extended, such as about two hours); the EIS condition is set to 1 MHz-1 kHz, and the perturbation voltage is set to 5 mV; after the test is completed, the data is processed by linear fitting to obtain the ion resistance of the separator.
[0148] The separator has low ion resistance, which is beneficial to improve the transmission speed of ions in the separator, and improve the cycle performance and rate performance of the battery.
[0149] The application also provides a preparation method of a secondary battery, comprising:
[0150] An electrode assembly including a positive electrode sheet, a negative electrode sheet, and a separator is assembled to obtain a secondary battery, the separator including a first polymer layer and a material layer disposed on the first polymer layer, the material layer including an inorganic material,
[0151] The inorganic material includes one or more of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium aluminum titanium germanium phosphate, lithium aluminum titanium tantalum phosphate, lithium tetrathiophosphate, lithium germanium phosphorus sulfide, lithium phosphorus sulfide chloride, iron oxide, copper oxide, titanium dioxide, tin dioxide, manganese dioxide, zinc oxide, zirconium dioxide, chromium nitride, vanadium nitride, nickel nitride, iron nitride, graphene oxide, graphite oxide, fluorinated graphite, fluorinated graphene, fluorinated carbon nanotubes, and fluorinated carbon fibers.
[0152] The material layer in the separator of the secondary battery absorbs lithium dendrites in contact with the material layer, converts sharp lithium dendrites into other lithium compounds, reduces the risk of lithium dendrites continuing to pierce the separator, and improves the cycle performance of the battery at high rates.
[0153] In some embodiments, the method for preparing the separator is as follows:
[0154] Step a: using a co-extrusion process, a first polymer layer raw material, a material layer raw material, and a second polymer layer raw material are used to obtain a composite sheet layer;
[0155] Step b: the composite sheet layer is subjected to a stretching treatment to form a film;
[0156] Step c: the film is subjected to an extraction and heat setting treatment to obtain a separator.
[0157] The material layer raw material includes the inorganic material,
[0158] The separator includes a first polymer layer, a material layer, and a second polymer layer, and the material layer is located between the first polymer layer and the second polymer layer.
[0159] The above preparation method can obtain a separator including a first polymer layer, a material layer, and a second polymer layer. The material layer includes an inorganic material that can react with lithium metal, which converts sharp lithium dendrites into other lithium compounds, reduces the risk of lithium dendrites continuing to pierce the separator, and improves the cycle performance of the battery at high rates. At the same time, the material layer is located between the first polymer layer and the second polymer layer, which can improve the safety performance of the material layer and further improve the cycle performance of the battery.
[0160] In some embodiments, step a specifically includes: after the first polymer layer raw material, the material layer raw material, and the second polymer layer raw material are separately melt blended, they are co-extruded through a multi-channel co-extrusion die to obtain the composite sheet layer.
[0161] In some embodiments, the first polymer layer raw material comprises the first polymer and a porogen, the material layer raw material comprises the third polymer and an inorganic material, and the second polymer layer raw material comprises the third polymer and the porogen.
[0162] The first polymer layer raw material and the second polymer layer raw material comprise a porogen, which is extracted in the extraction stage to leave micropores in the polymer layer, thereby improving the air permeability and porosity of the separator.
[0163] In some embodiments, the porogen comprises one or more of polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, mineral oil, kerosene, decalin, sodium chloride, potassium carbonate, lithium chloride.
[0164] In some embodiments, the mass content of the porogen is 0.1%-5% based on the mass of the first polymer layer raw material.
[0165] In some embodiments, the mass content of the porogen is 0.1%-5% based on the mass of the second polymer layer raw material.
[0166] The addition of a suitable mass of porogen to each polymer layer raw material facilitates the formation of a separator having a suitable air permeability value and porosity.
[0167] In some embodiments, the first polymer layer raw material, the material layer raw material, or the second polymer layer raw material each independently comprises one or more of polyethylene, polypropylene, polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride.
[0168] In some embodiments, the first polymer layer raw material and / or the second polymer layer raw material further comprises an antioxidant.
[0169] In some embodiments, the antioxidant comprises one or more of tris(2,4-di-tert-butylphenyl) phosphite, triphenyl phosphite, n-octadecyl beta-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, [tetra-beta-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester.
[0170] The addition of an antioxidant to the raw material can effectively reduce the rate of thermal oxidation and photo-oxidation of the polymer layer, significantly improve the heat resistance and light resistance of the polymer layer, delay the degradation and aging process of the polymer layer, and prolong the service life of the separator.
[0171] In some embodiments, the mass content of the antioxidant is 0.2%-0.4% based on the mass of the first polymer layer raw material.
[0172] In some embodiments, the antioxidant has a mass content of 0.2%-0.4% based on the mass of the second polymer layer raw material.
[0173] In some embodiments, the first polymer layer raw material and / or the second polymer layer raw material further comprises a nucleating agent.
[0174] The nucleating agent is used for the formation of crystal nucleus in the polymer, generating a polymer layer with semi-crystalline state.
[0175] In some embodiments, the nucleating agent comprises one or more of phthalic acid, azelaic acid, adipic acid, and dibenzylidene sorbitol.
[0176] In some embodiments, the nucleating agent has a mass content of 0.1%-5% based on the mass of the first polymer layer raw material.
[0177] In some embodiments, the nucleating agent has a mass content of 0.1%-5% based on the mass of the second polymer layer raw material.
[0178] In some embodiments, the step c specifically comprises:
[0179] The thin film is subjected to extraction treatment to obtain a microporous film;
[0180] The microporous film is subjected to heat setting treatment to obtain the separator.
[0181] In some embodiments, the step c specifically comprises:
[0182] The thin film is subjected to heat setting treatment to obtain a first film;
[0183] The first film is subjected to extraction treatment to obtain the separator.
[0184] The secondary battery of the present application includes a lithium metal battery or a lithium secondary battery.
[0185] The secondary battery can be in the form of a battery cell, can be in the form of a battery module, and can be in the form of a battery pack. The battery module and the battery pack contain battery cells, and the battery pack can also contain battery modules.
[0186] Generally, the battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the charging and discharging of the battery, active ions are embedded and extracted between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet, mainly to prevent short circuiting between the positive and negative electrodes, while allowing ions to pass through. The positive electrode sheet, the negative electrode sheet, and the electrolyte can use existing products for metal ion batteries.
[0187] [Positive electrode sheet]
[0188] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer including a positive electrode active material.
[0189] As an example, the positive electrode current collector has two surfaces opposite in the thickness direction thereof, and the positive electrode film layer is disposed on either one or both of the two surfaces of the positive electrode current collector.
[0190] In some embodiments, the positive electrode current collector can employ a metal foil or a composite current collector. For example, as the metal foil, an aluminum foil can be employed. The composite current collector can include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer material base material such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0191] In some embodiments, the positive electrode active material can employ a positive electrode active material for a battery known in the art. As an example, the positive electrode active material can include at least one of a lithium-containing phosphate of an olivine structure, a lithium transition metal oxide, and a modified compound of each thereof. However, the present application is not limited to these materials, and other conventional materials that can be used as a positive electrode active material for a battery can also be used. These positive electrode active materials can be used alone only one or two or more thereof can be used in combination. Among them, examples of the lithium transition metal oxide can include, but are not limited to, lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (which can also be referred to simply as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (which can also be referred to simply as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (which can also be referred to simply as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (which can also be referred to simply as NCM622), LiNi 0.8 Co 0.1 Mn 0.1O2(also can be referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and modified compounds thereof, etc. Examples of the olivine-structured lithium-containing phosphate can include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4(also can be referred to as LFP)), a composite of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite of lithium manganese iron phosphate and carbon.
[0192] In some embodiments, the positive electrode film layer can further optionally include a binder. As an example, the binder can include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene (HFP)-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0193] In some embodiments, the positive electrode film layer can further optionally include a conductive agent. As an example, the conductive agent can include at least one of super P, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0194] In some embodiments, the positive electrode tab can be prepared by dispersing the above-mentioned components for preparing the positive electrode tab, such as the positive electrode active material, the conductive agent, the binder, and any other components, in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector, and then performing processes such as drying, cold pressing, etc. to obtain the positive electrode tab.
[0195] [Negative electrode tab]
[0196] The negative electrode tab includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.
[0197] As an example, the negative electrode current collector has two surfaces opposite in the thickness direction thereof, and the negative electrode film layer is disposed on either one or both of the two opposite surfaces of the negative electrode current collector.
[0198] In some embodiments, the negative current collector can employ a metal foil or a composite current collector. For example, as a metal foil, a copper foil can be employed. The composite current collector can include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer material base layer such as a base layer of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0199] In some embodiments, the negative active material is metallic lithium.
[0200] In some embodiments, the negative active material can be an alloy of metallic lithium and other metal or non-metal elements. The metal elements include any one or more of tin (Sn), zinc (Zn), aluminum (Al), magnesium (Mg), silver (Ag), gold (Au), gallium (Ga), indium (In), and platinum (Pt). The metalloid elements include one or more of boron (B), carbon (C), and silicon (Si).
[0201] In some embodiments, the negative electrode sheet can be prepared by coating the above negative active material on the negative current collector by a rolling method, and then cutting to obtain the negative electrode sheet.
[0202] In some embodiments, the negative electrode sheet is a metallic lithium sheet.
[0203] [Electrolyte]
[0204] The electrolyte functions to conduct ions between the positive electrode sheet and the negative electrode sheet. The type of electrolyte is not specifically limited in the present application and can be selected as needed. For example, the electrolyte can be in a liquid state, a gel state, or a solid state.
[0205] In some embodiments, the electrolyte employs an electrolytic solution. The electrolytic solution includes an electrolyte salt and a solvent.
[0206] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonylimide, lithium bistrifluoromethylsulfonylimide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorobisoxalate borate, lithium bisoxalate borate, lithium difluorodibisoxalate phosphate, and lithium tetrafluorodibisoxalate phosphate.
[0207] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0208] In some embodiments, the electrolyte can further optionally include an additive. For example, the additive can include a negative electrode film-forming additive, a positive electrode film-forming additive, and can further include an additive capable of improving certain performance of the battery, such as an additive for improving overcharge performance of the battery, an additive for improving high-temperature or low-temperature performance of the battery, etc.
[0209] [Secondary battery]
[0210] In one embodiment of the present application, a secondary battery is provided, which includes a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte.
[0211] In some embodiments, the secondary battery is a lithium ion battery or a lithium metal battery. During charging and discharging of the battery, active ions are intercalated and deintercalated between the positive electrode sheet and the negative electrode sheet. The electrolyte functions to conduct ions between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet, and functions to prevent short circuiting between the positive and negative electrodes, while allowing ions to pass through.
[0212] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be made into an electrode assembly through a roll-pressing process or a stacking process.
[0213] In some embodiments, the secondary battery can include an outer package. The outer package can be used to encapsulate the electrode assembly and the electrolyte described above.
[0214] In some embodiments, the outer package of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery can also be a soft package, such as a pouch-type soft package. The material of the soft package can be plastic, and as plastic, polypropylene, polybutylene terephthalate, polybutylene succinate, etc. can be listed.
[0215] The shape of the secondary battery is not particularly limited in the present application, and can be cylindrical, square, or any other arbitrary shape. For example, Figure 3 is a secondary battery 5 of a square structure as an example.
[0216] In some embodiments, reference is made to Figure 4The outer package can include a housing 51 and a cover plate 53. The housing 51 can include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 can be arranged on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet, and the separator can form the electrode assembly 52 through a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and the number can be selected by a person skilled in the art according to the actual needs.
[0217] In some embodiments, the secondary battery can be assembled into a battery module, and the number of secondary batteries contained in the battery module can be one or more, and the specific number can be selected by a person skilled in the art according to the application and capacity of the battery module.
[0218] Figure 5 The battery module 4 is an example. Referring to Figure 5 In the battery module 4, a plurality of secondary batteries 5 can be arranged in sequence along the length direction of the battery module 4. Of course, other arbitrary arrangements can also be used. Further, the plurality of secondary batteries 5 can be fixed by fasteners.
[0219] Optionally, the battery module 4 can further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0220] In some embodiments, the above-mentioned battery module can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by a person skilled in the art according to the application and capacity of the battery pack.
[0221] Figure 6 and Figure 7 The battery pack 1 is an example. Referring to Figure 6 and Figure 7 The battery pack 1 can include a battery box and a plurality of battery modules 4 arranged in the battery box. The battery box includes an upper box body 2 and a lower box body 3, and the upper box body 2 can be arranged on the lower box body 3 to form a closed space for receiving the battery module 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0222] In addition, the application also provides a power utilization device, which comprises at least one of the secondary battery, the battery module, or the battery pack provided by the application. The secondary battery, the battery module, or the battery pack can be used as a power supply of the power utilization device, or can be used as an energy storage unit of the power utilization device. The power utilization device can include a mobile device (such as a mobile phone, a notebook computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc., but is not limited thereto.
[0223] As the power utilization device, the secondary battery, the battery module, or the battery pack can be selected according to the use requirement thereof.
[0224] Figure 8 The power utilization device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirement of high power and high energy density of the secondary battery for the power utilization device, the battery pack or the battery module can be used.
[0225] The device as another example can be a mobile phone, a tablet computer, a notebook computer, etc. The device usually requires thinning, and the secondary battery can be used as a power supply.
[0226] Example
[0227] Hereinafter, the embodiments of the application are described. The embodiments described below are exemplary and are only used to explain the application, and cannot be understood as a limitation of the application. If the specific technology or condition is not indicated in the embodiments, the technology or condition described in the literature in the art or according to the product instruction is used. If the reagent or instrument is not indicated by the manufacturer, it is a conventional product that can be obtained by market purchase.
[0228] I. Preparation method
[0229] Example 1
[0230] 1) Separator
[0231] The inorganic material titanium dioxide (volume particle size distribution Dv50 is 50 nm), polyethylene with a weight average molecular weight of 1.6 million, and a polyvinylpyrrolidone (PVP) pore former are respectively dispersed in a high-speed mixer at a mass ratio of 15:85:1 to obtain a material layer raw material; the polyethylene with a weight average molecular weight of 1.6 million, the nucleating agent terephthalic acid, the antioxidant tris(2,4-di-tert-butylphenyl) phosphite, and the polyvinylpyrrolidone (PVP) pore former are respectively dispersed in a high-speed mixer at a mass ratio of 99:0.7:0.3:1 to obtain a first polymer layer raw material and a second polymer layer raw material;
[0232] The first polymer layer raw material, the material layer raw material and the second polymer layer raw material are melt-blended and plasticized and transported through an eccentric rotor extruder at a temperature of 200℃, and respectively enter a three-layer co-extrusion die, wherein the blend of the first polymer layer raw material and the second polymer layer raw material enters the outer two sides, and the material layer raw material enters the inner side, and after cast cooling, a composite sheet layer is formed, wherein the mass ratio of the extrusion amount of the first polymer layer raw material, the extrusion amount of the material layer raw material and the extrusion amount of the second polymer layer raw material is 1:2:1.
[0233] The obtained composite sheet layer is stretched on a synchronous bidirectional stretching machine, the stretching ratio is 5x5, the stretching temperature is 118℃, and then heat setting is carried out at 130℃, the pressure is 10MPa, and the time is 60min, to obtain a first film.
[0234] The obtained first film is subjected to dichloromethane ultrasonic extraction, alcohol immersion, deionized water leaching and drying to obtain an isolation film.
[0235] 2) Preparation of positive electrode sheet
[0236] The positive electrode active material lithium iron phosphate, the conductive agent carbon black (Super P) and the binder polyvinylidene fluoride (PVDF) are mixed uniformly in a proper amount of solvent N-methyl pyrrolidone (NMP) at a mass ratio of 8:1:1 to obtain a positive electrode slurry, the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and through the processes of drying, cold pressing, slitting and cutting, a positive electrode sheet is obtained. The positive electrode surface density is 0.207mg / mm 2 , and the compacted density is 3.5g / cm 3 .
[0237] 3) Preparation of negative electrode sheet
[0238] The metal lithium sheet is used as the negative electrode sheet.
[0239] 4) Preparation of electrolyte
[0240] The ethylene carbonate (EC), the methyl ethyl carbonate (EMC) and the diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte, wherein the concentration of LiPF6 is 1mol / L.
[0241] 5) Preparation of battery
[0242] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, with the separator between the positive electrode sheet and the negative electrode sheet to play a separating role, to obtain an electrode assembly, wherein the diameter of the positive electrode sheet is 14 mm, the diameter of the lithium sheet is 16 mm, and the diameter of the separator is 16.5 mm; the electrode assembly is placed in an outer package, and the prepared electrolyte is injected into the dried electrode assembly, and the battery is obtained through vacuum packaging, standing, formation, shaping, and other processes.
[0243] Example 2
[0244] Compared with Example 1, the polyvinylidene fluoride with a weight average molecular weight of 450,000 is used to replace the polyethylene with a weight average molecular weight of 1.6 million in the material layer raw material, and other parameters are shown in Table 1.
[0245] Examples 3-6
[0246] Compared with Example 1, titanium dioxide in the material layer raw material is replaced by lithium titanium aluminum phosphate (volume particle size distribution Dv50 is 500 nm), iron nitride (volume particle size distribution Dv50 is 100 nm), graphite fluoride (volume particle size distribution Dv50 is 1000 nm, the number ratio of C atoms to F atoms is 1:1), and graphene oxide (volume particle size distribution Dv50 is 1000 nm, the number ratio of C atoms to O atoms is 2:1) in Examples 3-6, and other parameters are shown in Table 1.
[0247] Examples 7-10
[0248] Compared with Example 3, the mass ratio of lithium titanium aluminum phosphate to polyethylene in the material layer raw material is adjusted to 5:95, 10:90, 40:60, and 50:50 in Examples 7-10, and other parameters are shown in Table 1.
[0249] Examples 11-14
[0250] Compared with Example 3, the thickness ratio of the first polymer layer, the material layer, and the second polymer layer is adjusted by adjusting the extrusion amount of the first polymer layer raw material, the mass ratio of the extrusion amount of the material layer raw material to the extrusion amount of the second polymer layer raw material in Examples 11-14, and other parameters are shown in Table 1.
[0251] Example 15
[0252] Compared with Example 1, the difference lies in the adjustment of the preparation of the separator and the preparation process of the battery, which is as follows:
[0253] The polyethylene with a weight average molecular weight of 1.6 million, nucleating agent terephthalic acid, antioxidant tris (2, 4-di-tert-butylphenyl) phosphite and polyvinylpyrrolidone (PVP) pore forming agent were dispersed in a high-speed mixer according to a mass ratio of 99:0.7:0.3:1 to obtain a first polymer layer raw material;
[0254] The first polymer layer raw material was melt blended and plasticized by an eccentric rotor extruder at a temperature of 200 DEG C and transported into a single-layer extrusion die, and then the film layer was obtained after being cast and cooled;
[0255] The obtained film layer was stretched on a synchronous biaxial stretching machine at a stretching ratio of 5x5 and a stretching temperature of 118 DEG C, and then heat set at 130 DEG C for 60 min under a pressure of 10 MPa to obtain a thin film.
[0256] The obtained thin film was extracted by dichloromethane under ultrasonic, soaked in alcohol, rinsed with deionized water, and dried to obtain a first polymer layer.
[0257] The inorganic material titanium dioxide (volume particle size distribution Dv50 is 50 nm) and polyvinylidene fluoride with a weight average molecular weight of 450000 were dispersed in DMF solvent according to a mass ratio of 15:85, the formed slurry was coated on the first polymer layer with a thickness of 6 μm, the thickness of the material layer was adjusted to 6 μm by controlling the thickness of the scraper, and then air dried at room temperature, and finally vacuum dried in a vacuum oven at 60 DEG C for 24 h to obtain a separator.
[0258] The above positive electrode sheet, separator, and negative electrode sheet were stacked in order, the separator was placed between the positive and negative electrode sheets to play a separating role, and then an electrode assembly was obtained, wherein the diameter of the positive electrode sheet was 14 mm, the diameter of the lithium sheet was 16 mm, the diameter of the separator was 16.5 mm, and the material layer of the separator was arranged on the surface of the first polymer layer close to the positive electrode sheet; the electrode assembly was placed in an outer package, the above prepared electrolyte was injected into the dried electrode assembly, and the battery was obtained after vacuum packaging, standing, formation, shaping and other processes.
[0259] Example 16
[0260] Compared with example 1, the difference lies in adjusting the orientation of the material layer in the separator,
[0261] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, the separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and then an electrode assembly is assembled, wherein the diameter of the positive electrode sheet is 14 mm, the diameter of the lithium metal sheet is 16 mm, the diameter of the separator is 16.5 mm, and the material layer of the separator is arranged on the surface of the first polymer layer close to the negative electrode sheet; the electrode assembly is placed in an outer package, the prepared electrolyte is injected into the dried electrode assembly, and through processes such as vacuum packaging, standing, formation, and shaping, a battery is obtained.
[0262] Example 17
[0263] Compared with Example 1, the separator and the preparation method of the secondary battery are adjusted, and the specific adjustment is as follows:
[0264] The inorganic material titanium dioxide (volume particle size distribution Dv50 is 50 nm), polyethylene with a weight average molecular weight of 1.6 million, and a polyvinylpyrrolidone (PVP) porogen are fully dispersed in a high-speed mixer at a mass ratio of 15:85:1 to obtain a material layer raw material; the polyethylene with a weight average molecular weight of 1.6 million, the nucleating agent terephthalic acid, the antioxidant tris(2,4-di-tert-butylphenyl) phosphite, and the polyvinylpyrrolidone (PVP) porogen are fully dispersed in a high-speed mixer at a mass ratio of 99:0.7:0.3:1 to obtain a first polymer layer raw material;
[0265] The first polymer layer raw material and the material layer raw material are melt-blended and plasticized and transported by an eccentric rotor extruder at a temperature of 200 DEG C, respectively enter a two-layer co-extrusion die, and after casting cooling, a composite sheet layer is formed, wherein the mass ratio of the extrusion amount of the first polymer layer raw material to the extrusion amount of the material layer raw material is 1:1;
[0266] The obtained composite sheet layer is stretched on a synchronous bidirectional stretching machine at a stretching ratio of 5x5 and a stretching temperature of 118 DEG C, and then heat setting is performed at 130 DEG C, the pressure is 10 MPa, and the time is 60 min to obtain a first film;
[0267] The obtained first film is subjected to dichloromethane ultrasonic extraction, alcohol immersion, deionized water leaching, and drying to obtain a separator.
[0268] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, the separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and then an electrode assembly is assembled, wherein the diameter of the positive electrode sheet is 14 mm, the diameter of the lithium metal sheet is 16 mm, the diameter of the separator is 16.5 mm, and the material layer of the separator is arranged on the surface of the first polymer layer close to the negative electrode sheet; the electrode assembly is placed in an outer package, the prepared electrolyte is injected into the dried electrode assembly, and through processes such as vacuum packaging, standing, formation, and shaping, a battery is obtained.
[0269] Example 18
[0270] Compared with Example 1, the difference is that the preparation process of the separator is adjusted as follows:
[0271] Polyethylene with a weight average molecular weight of 1.6 million, nucleating agent terephthalic acid, antioxidant tris (2, 4-di-tert-butylphenyl) phosphite and polyvinylpyrrolidone (PVP) pore former are fully dispersed in a high-speed mixer according to a mass ratio of 99:0.7:0.3:1 to obtain a polymer layer raw material;
[0272] The base film raw material is melt blended and plasticized and transported through an eccentric rotor extruder at a temperature of 200°C, enters a single-layer extrusion die, enters the single-layer extrusion die, and after casting cooling, a sheet layer is obtained;
[0273] The obtained sheet layer is stretched on a synchronous double-direction stretching machine with a stretching ratio of 5x5 and a stretching temperature of 118°C, and then heat set at 130°C with a pressure of 10 MPa for 60 min to obtain a thin film;
[0274] The obtained thin film is extracted by dichloromethane ultrasonic extraction, soaked in alcohol, rinsed with deionized water, and dried to obtain a polymer layer.
[0275] Inorganic material titanium dioxide (volume particle size distribution Dv50 is 50 nm), polyvinylidene fluoride with a weight average molecular weight of 450,000 and DMF solvent are dispersed according to a mass ratio of 15:85, the formed slurry is coated on a polymer layer with a thickness of 3 μm, the thickness of the material layer is adjusted to 6 μm by controlling the thickness of the scraper, then another polymer layer with a thickness of 3 μm is used to cover the surface, and then air-dried at room temperature, and finally vacuum dried in a vacuum oven at 60°C for 24 h, and then taken out to obtain a separator.
[0276] Comparative Example 1
[0277] Compared with Example 1, the preparation method of the separator is adjusted as follows:
[0278] Polyethylene with a weight average molecular weight of 1.6 million, nucleating agent terephthalic acid, antioxidant tris (2, 4-di-tert-butylphenyl) phosphite and polyvinylpyrrolidone (PVP) pore former are fully dispersed in a high-speed mixer according to a mass ratio of 99:0.7:0.3:1 to obtain a polymer layer raw material;
[0279] The base film raw material is melt blended and plasticized and transported through an eccentric rotor extruder at a temperature of 200°C, enters a single-layer extrusion die, enters the single-layer extrusion die, and after casting cooling, a sheet layer is obtained;
[0280] The obtained sheet layer is stretched on a synchronous bidirectional stretching machine, the stretching ratio is 5x5, the stretching temperature is 118℃, and then heat setting is carried out at 130℃, the pressure is 10MPa, and the time is 60min, to obtain a film.
[0281] The obtained film is extracted by dichloromethane ultrasonically, soaked in alcohol, rinsed with deionized water, and dried to obtain a polymer layer with a thickness of 12μm.
[0282] II. Test method
[0283] 1. Cycle performance at high rate
[0284] At 25℃, the button cell is charged at 2C constant current to 3.65V, then charged at 3.65V constant voltage to the current of 0.05C, and then discharged at 0.33C constant current to 2.5V, which is one charge-discharge cycle. The discharge capacity of the first cycle of the button cell is recorded. The button cell is charged and discharged according to the above method for 100 cycles, and the discharge capacity of the 100th cycle is recorded. The discharge capacity retention rate of the button cell is calculated by the following formula:
[0285] Discharge capacity retention rate = discharge capacity of the 100th cycle / discharge capacity of the first cycle x 100%.
[0286] III. Analysis of test results of each example and comparative example
[0287] The separators and secondary batteries of each example and comparative example are prepared according to the above method, and each parameter is measured, and the results are shown in the following table.
[0288] Table 1
[0289]
[0290]
[0291] Table 2
[0292]
[0293] The separator in the secondary battery of the embodiments 1-18 of the present application includes a first polyethylene layer and a material layer disposed on the first polymer layer, and the material layer includes an inorganic material of titanium dioxide, lithium aluminum titanium phosphate, iron nitride, fluorinated graphite or graphene oxide.
[0294] As can be seen from the comparison of examples 1-18 and comparative example 1, the separator including the material layer can reduce the ion impedance of the separator, improve the cycle performance of the battery at high rate, and prolong the service life of the battery.
[0295] As can be seen from the comparison between Example 16 and Example 15, the material layer of the separator is arranged on the side surface of the first polymer layer close to the negative electrode tab, which can further improve the cycle performance of the battery at high rate and prolong the service life of the battery.
[0296] As can be seen from the comparison between Example 17 and Example 16, Example 2 and Example 18, the difference between the pore amount of the material layer and the pore amount of the first polymer layer in the longitudinal section view of the separator is less than or equal to 10%, which can reduce the ion impedance of the separator and improve the cycle performance of the battery at high rate.
[0297] As can be seen from the comparison between Example 2 and Example 17, the separator further comprises the second polymer layer, which can further improve the cycle performance of the battery at high rate and prolong the service life of the battery.
[0298] As can be seen from Example 3, Example 7-10, the mass content of lithium aluminum titanium phosphate is 5%-50% and the mass content of polyethylene is 50%-95% based on the total mass of the material layer, the separator has low ion impedance and the battery has good cycle performance at high rate. As can be seen from the comparison between Example 3, Example 8-10 and Example 7, the mass content of lithium aluminum titanium phosphate is 10%-50% and the mass content of polyethylene is 50%-90% based on the total mass of the material layer, which can further reduce the ion impedance of the separator, improve the cycle performance of the battery at high rate and comprehensively improve the cycle performance and rate performance of the battery.
[0299] As can be seen from Example 3, Example 11-14, the thickness ratio of the first polymer layer, the material layer and the second polymer layer is 1:(1-3):(0.8-1.2), the separator has low ion impedance and the battery has good cycle performance at high rate. As can be seen from the comparison between Example 3, Example 12-13 and Example 11, 14, the thickness ratio of the first polymer layer, the material layer and the second polymer layer is 1:(1.5-2.5):(0.8-1.2), which can further reduce the ion impedance of the separator and improve the cycle performance of the battery at high rate.
[0300] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and embodiments having the same technical idea and playing the same role and effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, within the scope of the main idea of the present application, various modifications of the embodiments, combination of part of the constituent elements in the embodiments to construct other ways can also be included in the scope of the present application.
Claims
1. A secondary battery characterized by comprising: The separator comprises a positive electrode sheet, a negative electrode sheet, and a separator, the separator is located between the positive electrode sheet and the negative electrode sheet, the separator comprises a first polymer layer and a material layer arranged on the first polymer layer, the material layer comprises inorganic material, The inorganic material comprises one or more of lithium titanium aluminum phosphate, lithium germanium aluminum phosphate, lithium titanium germanium aluminum phosphate, lithium titanium tantalum aluminum phosphate, lithium tetra-thiophosphate, lithium germanium phosphorus sulfide, lithium phosphorus sulfide chloride, iron oxide, copper oxide, titanium dioxide, tin dioxide, manganese dioxide, zinc oxide, zirconium dioxide, chromium nitride, vanadium nitride, nickel nitride, iron nitride, graphene oxide, graphite oxide, fluorinated graphite, fluorinated graphene, fluorinated carbon nanotube, and fluorinated carbon fiber.
2. The secondary battery according to claim 1, characterized by The material layer is arranged on one side surface of the first polymer layer close to the negative electrode sheet.
3. The secondary battery according to claim 1 or 2, characterized by In a longitudinal section view of the separator, the difference between the porosity of the material layer and the porosity of the first polymer layer is less than or equal to 10%.
4. The secondary battery according to any one of claims 1 to 3, characterized by, In a longitudinal section view of the separator, the porosity of the material layer is 10%-30%.
5. The secondary battery according to any one of claims 1 to 4, characterized by, In a longitudinal section view of the separator, the porosity of the first polymer layer is 10%-30%.
6. The secondary battery according to any one of claims 3 to 5, characterized by The separator further comprises a second polymer layer, and the material layer is located between the first polymer layer and the second polymer layer.
7. The secondary battery according to claim 6, characterized by In a longitudinal section view of the separator, the difference between the porosity of the material layer and the porosity of the first polymer layer is less than or equal to 10% and / or the difference between the porosity of the material layer and the porosity of the second polymer layer is less than or equal to 10%.
8. The secondary battery according to claim 6 or 7, characterized by In a longitudinal section view of the separator, the porosity of the material layer is 10%-30%.
9. The secondary battery according to any one of claims 6 to 8, characterized by, In a longitudinal section view of the separator, the porosity of the first polymer layer and / or the porosity of the second polymer layer is 10%-30%.
10. The secondary battery according to any one of claims 1 to 9, characterized by The volume distribution particle size Dv50 of the inorganic material is 50 nm-5000 nm.
11. The secondary battery according to any one of claims 1 to 9, characterized by The volume distribution particle size Dv50 of the inorganic material is 50 nm-1000 nm.
12. The secondary battery according to any one of claims 1 to 11, characterized by The material layer further comprises a third polymer, the mass content of the inorganic material is 5%-50% based on the mass of the material layer; and / or, the mass content of the third polymer is 50%-95%.
13. The secondary battery according to claim 12, characterized by The mass content of the inorganic material is 10%-50% and / or the mass content of the third polymer is 50%-90% based on the mass of the material layer.
14. The secondary battery according to claim 12 or 13, characterized by The first polymer layer comprises a first polymer, and the second polymer layer comprises a second polymer, The first polymer, the second polymer, and the third polymer each independently comprise one or more of polyethylene, polypropylene, polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl chloride.
15. The secondary battery according to claim 14, characterized by The first polymer, the second polymer, and the third polymer comprise polymers with the same material.
16. The secondary battery according to any one of claims 6 to 15, characterized by The thickness ratio of the first polymer layer, the material layer, and the second polymer layer is 1:(1-3):(0.8-1.2).
17. The secondary battery according to any one of claims 6 to 15, characterized by The thickness ratio of the first polymer layer, the material layer, and the second polymer layer is 1:(1.5-2.5):(0.8-1.2).
18. The secondary battery according to any one of claims 6 to 17, characterized by, The thickness of the first polymer layer is 2.5-4.5 μm; and / or, the thickness of the material layer is 3.5-7.5 μm; and / or, the thickness of the second polymer layer is 2.5-4.5 μm.
19. The secondary battery according to any one of claims 1 to 18, characterized by The thickness of the separator is 5-25 μm.
20. The secondary battery according to any one of claims 1 to 18, characterized by The thickness of the separator is 10-15 μm.
21. A method of producing a secondary battery, characterized by, Comprising: Assembling an electrode assembly comprising a positive electrode sheet, a negative electrode sheet and a separator to obtain a secondary battery, the separator comprising a first polymer layer and a material layer disposed on the first polymer layer, the material layer comprising an inorganic material, The inorganic material comprises one or more of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium aluminum titanium germanium phosphate, lithium aluminum titanium tantalum phosphate, lithium tetrathiophosphate, lithium germanium phosphorus sulfide, lithium phosphorus sulfide chloride, iron oxide, copper oxide, titanium dioxide, tin dioxide, manganese dioxide, zinc oxide, zirconium dioxide, chromium nitride, vanadium nitride, nickel nitride, iron nitride, graphene oxide, graphite oxide, fluorinated graphite, fluorinated graphene, fluorinated carbon nanotubes, fluorinated carbon fibers.
22. The method of claim 21, wherein, The preparation method of the separator is as follows: Step a: using a co-extrusion process to obtain a composite sheet layer from a first polymer layer raw material, a material layer raw material and a second polymer layer raw material; Step b: stretching the composite sheet layer to form a film; Step c: extracting and heat setting the film to obtain a separator. The material layer raw material comprises the inorganic material, The separator comprises a first polymer layer, a material layer and a second polymer layer, and the material layer is located between the first polymer layer and the second polymer layer.
23. An electrical device, comprising: The secondary battery of any one of claims 1-20 or the secondary battery prepared by the preparation method of claims 21 or 22.